Youth in the Future of the Nation – Image of Youth in Poland in 1956 in the Context of the Polish Film Chronicle - Martinek, Ewa (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
The Polish Film Chronicle was broadcast in 1944–1994. It was supposed to serve as an information function, but quite soon the authorities realized about the possibilities of manipulating the society through broadcasted content and “enriching” it with comments.Despite the fact that the PKF has become the propaganda tube of the authorities, the influence of the thaw was also visible in the themes of the chronicle. The subject of addiction was discussed more and more honestly and more honestly about the human being and the surrounding reality. Among the socio-cultural issues presented, a lot has been devoted to youth.The image of students shown in the PKF is a picture of active people, developing on many levels, engaging not only in scientific issues, but also in sport and broadly understood culture. Most threads concern students. It is worth noting, however, that the reason for the dominance of materials devoted to the academic community over materials concerning rural and working youth is the easy separation of students from the broadly defined Youth. Young people who did not undertake further education, working in factories or in the countryside, in some sense ceased to function as young people.Apprentices of apprenticeship schools quickly received labor orders, becoming apprentices and later employees of the establishments. They were simply workers, and thus included in other social groups. The situation was similar in the case of rural youth who remained on farms, thus becoming the main heroes and recipients of the content “about” and “for” the then peasant class.In the Polish Film Chronicle, when young people were criticized, they did not do it directly, they were hidden under frequently used terms of blaggards, rogues referring also to other social groups. Positive presentation of young people was consistent with the policy of the authorities proclaiming the slogan: youth the future of the nation, a man shaped according to a new scenario – in the spirit of communist ideology – was privileged in the eyes of the governing. A young engineer, peasant, laborer, teacher had a better chance of becoming a professional and social person resulting from the fact of being a young man.